2009
DOI: 10.17221/68/2009-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of agricultural subsidies in the Czech Republic and in the selected states of the European Union

Abstract: The Common Agricultural Policy has been implemented in order to guarantee the appropriate life quality for farmers and to preserve the European heritage. Costs of its realization amounted to 40% of the EU budget. The EU has not established the same conditions for all member states. The aim of the paper is to assess the influence of agricultural subsidies and the structure of production on the incomes of agricultural holdings and their comparison with the largest producers in the EU with similar production stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 17 publications
1
13
0
1
Order By: Relevance
“…It is usual to analyze the employment (Bielik, Rajčániová, 2008;Riguelle et al, 2007;Blien, Wolf, 2002;Dinc, Haynes, 1999), the added value (Esteban, 2000), labour productivity (Maudos et al, 2008) or other (Střeleček et al, 2009) as an analysed variable. Berzeg (1978) and Knudsen (2000) based the analysis on the model of relative change analysis.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…It is usual to analyze the employment (Bielik, Rajčániová, 2008;Riguelle et al, 2007;Blien, Wolf, 2002;Dinc, Haynes, 1999), the added value (Esteban, 2000), labour productivity (Maudos et al, 2008) or other (Střeleček et al, 2009) as an analysed variable. Berzeg (1978) and Knudsen (2000) based the analysis on the model of relative change analysis.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…In our later research, we are arriving at the conclusion that the lower agriculture performance of the new EU countries is caused mainly by the lower use of the fixed and variable assets and a lower effectiveness of their utilisation (Grznár 2014). Střeleček et al (2009) by means of the shift-share analysis, evaluate the influence of the supports/subsidies in agriculture and of the structure of agricultural production on incomes of businesses, while comparing the Czech Republic, Poland, Germany, and the Great Britain. They conclude that the Czech agriculture is competitive, because it has lower subsidies at lower costs.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…In this study, it is determined that the lower percentages of support level weaken the competitiveness of agricultural area, and the regeneration and modernization of agriculture. As a result, it is concluded that the subsidies which are applied according to type of production might affect the production diversity (Střeleček et al, 2009). A Premium support system is an alternative support model that can be applied by assuring stability in the sense of prices and the producer in agriculture of Turkey, depending on the research work of Sahinoz et al (2007).…”
Section: Introductionmentioning
confidence: 99%